Friendly Fire in a Simulated Firearms Task. (September 2013) - Wilson, Kyle; Head, James; Helton, William S.
Factors such as poor visibility, lack of situation awareness, and bad communication have been shown to contribute to friendly fire incidents. However, to the authors' knowledge, an individual's ability to inhibit their motor response of shooting when a non-target is presented has not been investigated. This phenomenon has been modeled empirically using the Sustained Attention to Response Task (SART; Robertson, Manly, Andrade, Baddeley, & Yiend, 1997) computer task. The SART is generally a high Go/low No-Go detection task whereby participants respond to numerous neutral stimuli and withhold to rare targets. In the current investigation, we further investigate the SART using a simulated small arms scenario to test whether lack of motor response inhibition can be modeled in a more ecologically valid environment. Additionally, we were interested in how error rates were impacted in low Go/high No-Go versions of the task. Thirteen university students completed a computer and simulated small arms scenario in a SART and low Go condition. Both the computer and small arms scenario revealed similar speedaccuracy trade-offs indicating participants' inability to halt their pre-potent responses to targets even in a more ecologically valid environment. The SART may be used in future studies to model friendly fire scenarios.